Feasibility Analysis of Converting Diesel Power Plants (PLTD) to Solar Power Plants (PLTS) on Seira Island in Order to Reduce Electricity Supply Costs - Syariffuddin Achmad; Lela Nurlaela Wati; Ira Geraldin (Eduvest - Journal of Universal Studies, 2026)
Seira Island still relies on Diesel Power Plants (PLTD) as its main source of electricity supply, which results in high operating costs, dependence on fossil fuels, and increasing greenhouse gas emissions. This condition highlights the need for more efficient, sustainable, and environmentally friendly alternative power plants. This research aims to analyze the technical and economic feasibility of converting the power generation system from PLTD to Solar Power Plants (PLTS) on Seira Island to reduce electricity supply costs. The research method used is a quantitative descriptive analysis with a feasibility study approach, which includes analyzing electrical energy needs, solar power capacity planning, and an economic feasibility evaluation using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) indicators. The data used are secondary data obtained from relevant agencies, technical reports of power plants, and supporting literature. The study results show that converting PLTD to solar power plants can significantly reduce the operational costs of power generation and decrease dependence on diesel fuel. Moreover, the economic analysis demonstrates that the solar power plant project on Seira Island is feasible to implement, with a positive NPV value, an IRR above the benchmark interest rate, and a relatively short investment payback period. Therefore, the conversion from PLTD to solar PV can serve as a strategic solution for providing sustainable and efficient electrical energy in remote island areas.